Education for Employability in the Health Tourism Industry: A Contribution of English Language Courses to Soft Skills Development - Radovanović, Aleksandra M.; Mitrović, Aleksandra B. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
Along with the growing demands on the tourism and hospitality market, soft skills have been increasingly stated as the main prerequisites for employability. Therefore, this study set out to investigate the health tourism students’ perceptions of the soft skills they possess with an emphasis on the contribution of English language courses to their development. The data were collected employing the tailor-made questionnaire which addressed 12 soft skills deemed the most necessary for the inclusion in the (health) tourism labour market. Students perceived their soft skills to be at an average to a moderately high level of development. Likewise, an average to a moderately high level of the contribution of English language instruction was noted. These findings indicate that there is much room for improvement and can be informative for various stakeholders in the education process. On the one hand, the study has revealed that the language courses have a favourable impact on soft skills development, and on the other, it has produced a relatively good representation of the enhancements to be made in this regard.